SAT0049 In vivo analysis of the synovial neoangiogenic processes and leukocyte trafficking, and their relationships with tissue histomorphology and cytokine content, at the earliest phases of development of an experimental model of antigen-induced arthritis. (23rd January 2014) - Fischetti, F.; De Nardo, D.; Durigutto, P.; Macor, P.; Grillo, A.; Fabris, B.; Carretta, R.
Abstract : Background: Chronic immune-mediated arthritis development is based upon the occurrence of both leukocyte tissue infiltration and neoangiogenesis. Proper evaluation of the pattern of development of leukocyte influx and newly expressed microvessels during the early phases of autoimmune synovitis might be of primary relevance. Objectives: We aimed to set up technical procedures for visualizing in vivo the occurrence of microvascular modifications, as well as for analyzing the parallel degree of leukocyte trafficking, further evaluating the relationships existing between these parameters and the extent of tissue damage scores and cytokine synovial fluid levels in the course of the early phases of an immune complex-mediated model of experimental arthritis, namely the antigen-induced arthritis (AIA). Methods: Following legal animal care policies, AIA was induced in the right knee joint of 20 Wistar male rats. At different time points, up to 10 days after arthritis induction, anesthetized rats underwent surgical preparation for the in vivo visualization of sub-patellar tendon synovial joint tissue, by using a videomicroscopy device suitable for analogic-digital conversion of videoimages. Microvessels shapes and diameters, and the interplay between leukocytes and endothelial cells, were analyzed respectively by intravenously injecting FITC-labelled bovine serum albumin or acridine orange, at pre-established concentrations. Microvessel and adhering/extravasated leukocyte numbers were compared with the degree of tissue damage score, of infiltrating neutrophils and of synovial fluid concentrations of TNF-α, IL-6, and MCP-1 as assessed from a parallel set of comparable AIA experimental settings (n=12 animals). Results: In the arthritic joints a significantly increased total number of microvessels (p<0, 001) was observed already after the third day of disease and this feature showed to be persistently evident along the entire period of clinical follow-up. A higher degree of vessels with diameter lower than 20μm (marker for capillary vessels) was also evidently detectable, reaching a peak number at he 5th day after arthritis induction. Morphologically deranged vessels, with branched and irregular patterns, were observed in the arthritic joints. Stable adhesion of fluoresceinated leukocytes to the endothelial layer of synovial microvessels was significantly increased (29±4 vs 8±6 cells/200μm; p<0, 01) soon after the 1st day of induced arthritis, and this difference further increased with a peak level at the 5th day after arthritis induction. Microvessels increase and leukocyte infiltration were significantly (p<0.01) related with the degree of damage score, of infiltrating neutrophils and of synovial fluid concentrations of TNF-alpha and MCP-1. Conclusions: The in vivo pattern of development of newly expressed microvessels and of leukocytes trafficking in the early evolving phases of an experimental model of arthritis was here described and related with some more commonly described ex vivo parameters of inflammation. This experimental approach could be helpful for analyzing more detailed arthritis-related molecular pathogenic mechanisms and vascular-targeted therapeutic interventions. Disclosure of Interest: None Declared